STRATEGI GURU PAI DALAM MENINGKATKAN IMAN DAN TAKWA SISWA - Suwartiningsih Suwartiningsih (Jurnal Paradigma, 2022)
The era of globalization has had many impacts on social life, namely in the form of positive impacts and negative impacts. Where these two impacts are very influential on students such as the advancement of technological tools that can be utilized by students to more easily access scientific information, but with the wrong use, technology can damage the quality of students, for example by opening pornographic features, practicing gambling. games, etc., so that this misuse can affect students' spiritual attitudes. So educational institutions as a forum for students must have a strategy in dealing with this era of globalization, by instilling more religious education. Moreover, PAI teachers must have strategies or be able to provide approaches to attract students' interest in religious learning in order to build a religious attitude in students.   Keywords: PAI Teacher Strategy, Improving Student Faith and Piety